Biotreatment efficiency, degradation mechanism and bacterial community structure in an immobilized cell bioreactor treating triclosan-rich wastewater. Issue 10 (29th April 2023) - Navrozidou, Efstathia; Remmas, Nikolaos; Melidis, Paraschos; Sylaios, Georgios; Ntougias, Spyridon
ABSTRACT: Biotreatment of triclosan is mainly performed in conventional activated sludge systems, which, however, are not capable of completely removing this antibacterial agent. As a consequence, triclosan ends up in surface and groundwater, constituting an environmental threat, due to its toxicity to aquatic life. However, little is known regarding the diversity and mechanism of action of microbiota capable of degrading triclosan. In this work, an immobilized cell bioreactor was setup to treat triclosan-rich wastewater. Bioreactor operation resulted in high triclosan removal efficiency, even greater than 99.5%. Nitrogen assimilation was mainly occurred in immobilized biomass, although nitrification was inhibited. Based on Illumina sequencing, Bradyrhizobiaceae, followed by Ferruginibacter, Thermomonas, Lysobacter and Gordonia, were the dominant genera in the bioreactor, representing 38.40 ± 0.62% of the total reads. However, a broad number of taxa (15 genera), mainly members of Xanthomonadaceae, Bradyrhizobiaceae and Chitinophagaceae, showed relative abundances between 1% and 3%. Liquid Chromatography coupled to Quadrupole Time-Of-Flight Mass Spectrometry (LC-QTOF-MS) resulted in the identification of catabolic routes of triclosan in the immobilized cell bioreactor. Seven intermediates of triclosan were detected, with 2, 4-dichlorophenol, 4-chlorocatechol and 2-chlorohydroquinone being the key breakdown products of triclosan. Thus, the immobilized cell bioreactor accommodated a diverse bacterial community capable of degrading triclosan. GRAPHICAL ABSTRACT: UF0001